Meningkatkan literasi informasi penulisan karya ilmiah mahasiswa melalui pelatihan zotero - Muhammad Erdiansyah Cholid Anjali; Zeni Istiqomah (Berkala Ilmu Perpustakaan dan Informasi, 2020)
Introduction. The purpose of this study is to examine a zotero training conducted by Universitas Muhammadiyah Yogyakarta (UMY) Library, information literacy skills, and the role of the zotero training on the literacy skills in students’ academic writing. Data Collection Method. The data collection method used was a descriptive qualitative with observation and interviews. The participants were students study of Master of Government Affairs and Administration program at UMY. Data Analysis. Data analysis was performed by validating the collected data which were then categorized based on the theory. Results and Discussions. The results showed that students received the zotero training well. The material provided in the training including the explanation of the Zotero concept, installation of the Zotero application, and utilization of the Zotero application were well understood. Conclusion. The ability of information literacy of students of Master of Government Affairs and Administration, which was initially limited, increases by the Zotero training involvement. These capabilities include how to identify information needs, access information, evaluate information, and use information effectively.